Prototyping with data - Biddulph, Matt (O'Reilly Media, 2011)
"If you're a new startup looking for investment, or a team at a large company seeking the green light for a new product, nothing convinces like real running code. But how do you solve the chicken-and-egg problem of filling your early prototype with real data? We'll discuss how to use open datasets and public web APIs as a proxy for the final product while you're still in the development stage."--Resource description page.